Inventario Florístico del sector de Buga bajo del bosque de Paquiestancia, Cayambe-Ecuador 2008 - León Jaramillo, Helen Tatiana (2013)
The research was maked in the area of Buga Bajo in the comunity of Paquiestancia, Canton Cayambe, in the Pichincha Province, the rates of heights are 3150 msnm to 3400 msnm. The area was searched in 10 squares of 100 m2 each one, the goal was make a significant area in our study. This project, guive us the opportunity, to get in touch with the native species, each of one have different uses like: medical uses, feed animals and humans, decoration, and mitic rituals. In the relationship with the squares, we determinate, that the major number of species are present in the square number 2 and he square number 3 with 22 native species, the middle one between square number 2 and square number 3 was the square number 5 and 6 with 35 species, and the lower number of of species that we found were in the square 10 with 10 species, we can understand this aspect, because when we find an area in wich the height are increased, we found species stronger and toller, that need more space and other aspect is that we found lest species.